Anti‐tumor effect of SLPI on mammary but not colon tumor growth1. Issue 2 (25th October 2012) - Amiano, Nicolás O.; Costa, María J.; Reiteri, R. Macarena; Payés, Cristian; Guerrieri, Diego; Tateosian, Nancy L.; Sánchez, Mercedes L.; Maffia, Paulo C.; Diament, Miriam; Karas, Romina; Orqueda, Andrés; Rizzo, Miguel; et al.
Abstract: Secretory leukocyte protease inhibitor (SLPI) is a serine protease inhibitor that was related to cancer development and metastasis dissemination on several types of tumors. However, it is not known the effect of SLPI on mammary and colon tumors. The aim of this study was to examine the effect of SLPI on mammary and colon tumor growth. The effect of SLPI was tested on in vitro cell apoptosis and in vivo tumor growth experiments. SLPI over‐expressing human and murine mammary and colon tumor cells were generated by gene transfection. The administration of murine mammary tumor cells over‐expressing high levels of SLPI did not develop tumors in mice. On the contrary, the administration of murine colon tumor cells over‐expressing SLPI, developed faster tumors than control cells. Intratumoral, but not intraperitoneal administration of SLPI, delayed the growth of tumors and increased the survival of mammary but not colon tumor bearing mice. In vitro culture of mammary tumor cell lines treated with SLPI, and SLPI producer clones were more prone to apoptosis than control cells, mainly under serum deprivation culture conditions. Herein we demonstrated that SLPI induces the apoptosis of mammary tumor cells in vitro and decreases the mammary but not colon tumor growth in vivo. Therefore, SLPI may be a new potential therapeutic tool for certain tumors, such as mammary tumors. J. Cell. Physiol. 228: 469–475, 2013. © 2012 Wiley Periodicals, Inc.